2016
DOI: 10.1111/prd.12180
|View full text |Cite
|
Sign up to set email alerts
|

Zirconia dental implants: where are we now, and where are we heading?

Abstract: Despite decades of titanium as the gold standard in oral implantology, the search for alternatives has been growing. High esthetic standards and increasing incidence of titanium allergies, along with a rising demand for metal‐free reconstructions, have led to the proposal of ceramics as potential surrogates. Following numerous experimental studies, zirconium dioxide (zirconia) has earned its place as a potential substitute for titanium in implantology. Yet, despite zirconia's excellent biocompatibility and tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
209
1
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(219 citation statements)
references
References 102 publications
(121 reference statements)
0
209
1
9
Order By: Relevance
“…Cionca et al reported a cumulative soft tissue complication rate of 0% in 76 zirconia implants placed in 52 patients . Literature evaluating the soft tissue interface around implants seems to favor zirconia implants over titanium, although further investigations are needed …”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Cionca et al reported a cumulative soft tissue complication rate of 0% in 76 zirconia implants placed in 52 patients . Literature evaluating the soft tissue interface around implants seems to favor zirconia implants over titanium, although further investigations are needed …”
Section: Discussioncontrasting
confidence: 46%
“…Currently, zirconium dioxide (zirconia) ceramics in dental implants are emerging as an alternative to titanium mainly due to superior soft tissue healing . The advantages of zirconia implants are the white color and the apparent less affinity to bacterial biofilm formation …”
Section: Introductionmentioning
confidence: 99%
“…Recently, zirconia (ZrO 2 ) has been introduced as an alternative to Ti‐based dental implant bodies or screws . Like Ti, ZrO 2 presents an oxide surface that is conducive to osseointegration to a similar degree as Ti .…”
mentioning
confidence: 99%
“…For example, the passage of time could influence the cells' phenotype much more than implant surfaces [49]. However, a recent review on zirconia implant outcomes concluded that early failure rate of zirconia implants was higher when compared with titanium ones [68].…”
Section: Discussionmentioning
confidence: 99%